Da'wah Expectations KH. Mahfud Ridwan in Developing Harmony Between Religious People in Semarang Regency 1984-2015 - Abrori Abrori; Ahmad Kharis; Kuni Barirotus Sa'adah (Lakpesdam PCNU Kota Salatiga, 2022)
The goal to be achieved in this study is to determine the condition of the people of Semarang Regency in the pre and post-dawa period of KH. Mahfud Ridwan, as well as knowing the da'wah of KH. Mahfud Ridwan in developing inter-religious harmony in 1984-2015. The research method used is descriptive qualitative with a historical approach. The data in this study were obtained through interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation and conclusion drawing. While the data validation technique in this study uses triangulation. The results showed that the condition of the district community before the preaching of KH. Mahfud Ridwan has started to be conducive and after his preaching he is getting better. KH. Mahfud Ridwan preached using the following methods: (1) Bil wisdom with a noble mind, wise, broad chested and a clean heart. The form of da'wah based on bil wisdom includes mobilizing the community through community and religious organizations including the NGO Desaku Maju Foundation, Gedangan Forum, FSUB and the SOBAT movement. Besides that, KH. Mahfud Ridwan also founded the Edi Mancoro Islamic Boarding School as an intermediary to spread benefits to the community by forming the character of students who have religious, national and community perspectives. (2) Bil mau'idzah hasanah by holding regular recitations, teaching in Islamic boarding schools and madrasas, cults and Islamic holidays. (3) Bil mujlah by holding discussion and dialogue activities that invite various interfaith figures.